A trend toward smaller optical angles and medial‐ocular distance in schizophrenia spectrum, but not in bipolar and major depressive disorders. Issue 4 (8th October 2016) - Wang, Yi; Deng, Yi; Li, Zhi; Li, Xu; Zhang, Chen‐yuan; Jin, Zhen; Fan, Ming‐xia; Compton, Michael T.; Cheung, Eric F. C.; Lim, Kelvin O.; Chan, Raymond C. K.
Abstract : Minor physical anomalies (MPAs) are subtle signs of fetal developmental abnormalities that have been considered to be among the most replicated risk markers for schizophrenia‐spectrum disorders. However, quantitative approaches are needed to measure craniofacial MPAs. The present study adopted an imaging‐based quantitative approach to examine craniofacial MPAs across the spectrum of schizophrenia and affective disorders, to address their sensitivity and specificity. We sampled 31 patients with schizophrenia, 30 of their unaffected relatives, and 30 individuals with schizotypal personality traits, as well as 37 non‐schizotypal controls. We also examined 17 patients with bipolar disorder and 19 patients with major depressive disorder. Five craniofacial MPAs were measured on anterior–posterior commissure‐aligned T1‐weighted images of an individual's native brain space: medial‐ocular distance, lateral‐ocular distance, optical angle, maximum skull length, and skull‐base width. Compared to non‐schizotypal controls, patients with schizophrenia and their relatives showed a trend toward having smaller optical angles and medial‐ocular distance, while no difference was found in patients with bipolar or major depressive disorders, suggesting some degree of specificity to schizophrenia. Our approach may benefit future research on craniofacial MPAs as risk markers for schizophrenia‐spectrum disorders, and may eventually be useful in strategies to enhance risk stratification using multiple risk markers.